Retrospective chart review‐based assessment scale for adverse childhood events and experiences. Issue 4 (17th November 2022) - Yamagishi, Mika; Satomura, Yoshihiro; Sakurada, Hanako; Kanehara, Akiko; Sakakibara, Eisuke; Okada, Naohiro; Koike, Shinsuke; Yagishita, Sho; Ichihashi, Kayo; Kondo, Shinsuke; Jinde, Seiichiro; Fukuda, Masato; et al.
Abstract: Aim: Adverse childhood experiences (ACEs) are highly prevalent in the general population, and their lifelong impact on physical and mental health is profound. In assessing ACEs, it is vital to consider the pathways and modalities by which an individual internalizes events as an adverse experience and its effects on their biological, psychological, and social function. However, conventional assessments of ACEs are inadequate in that they do not comprehensively assess the source of the adverse event and the pathway and mode of its impact on the individual. Methods: This study developed an original scale for ACEs that classifies the source of the event and the pathway and mode of its impact on the individual from a retrospective review of medical charts. We also used this scale to investigate the ACEs in 536 patients with psychiatric disorders (depression, bipolar disorder, and schizophrenia). Results: This scale consisted of 28 items, and its reliability and validity were sufficient. We also found that 45.9% of the patients studied had at least one ACE, ranging from 43.5% to 51.5% for all disorders. Psychological trauma (bullying) from peers was the most common cause at 27.2%. Conclusion: We developed a retrospective chart review‐based assessment tool for ACEs which enables the examination of the source of the events of ACEs and the pathways and modalities of their impact on the individual. The frequency of ACEs is high regardless of the type of psychiatric disorder, and horizontal trauma (bullying victimization) is as frequent as vertical trauma (parental maltreatment).